CO sensor based on polypyrrole functionalized with iron porphyrin - Paul, Santhosh; Amalraj, Francis; Radhakrishnan, S. (Synthetic Metals, 2009)
Polypyrrole (PPy) was chemically functionalized with 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron(III) chloride (FeTPPCl) with special interest on noxious carbon monoxide (CO) gas in ppm level. Controlled functionalization of PPy was achieved with incorporation of various concentrations of porphyrin. The resulted semiconducting material was well characterized by different techniques such as UV-vis spectroscopy, FTIR, GFAAS, XRD, and EDAX. The functionalized polypyrrole material on interdigitated electrode was experienced an immediate increase in resistance when exposed to carbon monoxide gas at very low concentration. The CO gas interacted very fast with the FeTPPCl functionalized PPy at room temperature (RT) and then slowly saturated. The response of these materials was not unidirectional, but reverses to the original resistance level when CO was removed from the test chamber. The highest response factor (Delta R/R(0) x 100) and lowest response time (t(50)) obtained are 12 and 169s, respectively. An optimum level of doping (1 mol% of FeTPPCl) was established for the highest sensitivity and the detection level is as low as 100ppm. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; Fe(III) porphyrin; polypyrrole

Polypyrrole functionalized with ferrocenyl derivative as a rapid carbon monoxide sensor - Paul, Santhosh; Chavan, Nayaku; Radhakrishnan, S. (Synthetic Metals, 2009)
A rapid carbon monoxide detection system was developed with the electrochemical functioncalization of polypyrrole (PPy) with ferrocenylmethyltrimethylammonium iodide (FTMA-I) as a co-dopant exhibits very high sensitivity to ppm levels of carbon monoxide gas and fast recovery under normal dry room temperature conditions. The co-dopant was synthesized mainly to incorporate into PPy electrochemically to modify the properties in order to sense carbon monoxide (CO) gas. The FTMA-I doped PPy exhibited the characteristics oxidation/reduction peaks for ferrocene in its cyclic voltammograms. The modified PPy films deposited on interdigited electrodes gave rapid sensitivity within a second to 300 ppm carbon monoxide gas and good sensitivity factor was observed even at 4 mmol of the functional groups in the polymer for 300 ppm carbon monoxide gas. This material detected the CO gas concentration as low as 100 ppm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; conducting polymer; polypyrrole